Features of social action in Soviet society on the example of the Great Patriotic War - Podyachev, Kirill V. (Journal of the Belarusian State University. Sociology, 2023)
In this article, on the example of a number of episodes of the initial period of the Great Patriotic War, the features of social action characteristic of Soviet society are considered. The war of 1941–1945 and the Great Victory to this day are perhaps the main ideological and cultural dominant of the mass consciousness in both the Russian Federation and the Republic of Belarus. Perhaps this is the only historical event that does not cause controversy. Almost all citizens, regardless of ethnicity, religious and political beliefs, recognise its significance, keep the memory of it and are proud of the contribution of their ancestors. The mass character of the «Immortal Regiment» annual event confirms this better than any polls. Based on the concept of social action paradigm invented by O. V. Aksenova, the author shows how exactly the actor’s action (that is, the independent, responsible behaviour of the acting subject) manifested itself not only in single heroic deeds, but in the work of the entire system of the Soviet state in such an extreme situation as a world war. The basis of the analysis was the memoirs of Soviet military leaders and the data given in the historical literature. The author comes to the conclusion that the actor’s form of social action, characteristic of Russian civilisation (free action limited only by values), not only manifested itself in the extreme conditions of the war, but became the main factor in achieving victory.
Keywords: sociology; history; civilisation; Soviet power; Great Patriotic War; social action; behavioural motivations